Fourteenth Annual Signature Event, June 15, 2019, Ad Astra [program and schedule of activities] - Symphony in the Flint Hills, Inc. (Symphony in the Flint Hills, 2019)
Program for the 2019 Symphony in the Flint Hills with information about the Stout Family's "Irma's Pasture", in scenic Chase County, Kansas, serving as the venue for this year's events. The program and schedule includes participating artists, notes from the Board of Directors and more. Also included are program notes for a performance of the Wahzhazhe Ballet, produced by Randy Tinker Smith, and a concert by the Kansas City Symphony under the direction of conductor Jason Seber, with special guest vocalist, recording artist Mirah.